Rapid chemoenzymatic route to glutamate transporter inhibitor l-TFB-TBOA and related amino acids. Issue 11 (28th February 2017) - Fu, Haigen; Younes, Sabry H. H.; Saifuddin, Mohammad; Tepper, Pieter G.; Zhang, Jielin; Keller, Erik; Heeres, André; Szymanski, Wiktor; Poelarends, Gerrit J.
Abstract : Rapid route tol -TFB-TBOA: Using only nine chemical transformations, we have managed to construct the complex amino acidl -TFB-TBOA starting from commercially available dimethyl acetylenedicarboxylate. Abstract : The complex amino acid (l - threo )-3-[3-[4-(trifluoromethyl)benzoylamino]benzyloxy]aspartate (l -TFB-TBOA) and its derivatives are privileged compounds for studying the roles of excitatory amino acid transporters (EAATs) in regulation of glutamatergic neurotransmission, animal behavior, and in the pathogenesis of neurological diseases. The wide-spread use ofl -TFB-TBOA stems from its high potency of EAAT inhibition and the lack of off-target binding to glutamate receptors. However, one of the main challenges in the evaluation ofl -TFB-TBOA and its derivatives is the laborious synthesis of these compounds in stereoisomerically pure form. Here, we report an efficient and step-economic chemoenzymatic route that gives access to enantio- and diastereopurel -TFB-TBOA and its derivatives at multigram scale.